The Social Class Differences Reflected On People’s Lives In The Snowpiercer Movie By Bong Joon Ho (Marxist Theory Analysis) - Thias Apriliani; Dedi Efendi; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2022)
This research studies about The Social Class Differences Reflected on People’s Lives in The Snowpiercer Movie. The purposes of this research are: (1) to describe about the division of social class differences to people’s lives on the Snowpiercer movie and (2) to analyze the impacts of social class differences on people’s lives on the Snowpiercer movie. This research used qualitative research method. In analyzing the data the researcher uses Marxist theory (1950).            The researcher found some data that were divided into two classes of society. The first one is the upper class as the bourgeoisie, in bourgeoisie class the researcher found out nine data. The second is the lower class as proletariat, the researcher found out six data, each of which reveals about bourgeoisie social life, lifestyle and behavior. In addition, the researcher also found the impact for people’s lives in the Snowpiercer movie such as from all the data presented, it can be concluded that social class are divided into two main classes and differentiated through the behavior, social life, and their goods. And those things cause the impact for people’s life in Snowpiercer movie which ultimately caused the deaths of both classes. A cannibalism, rebellion, and even population reduction as the impact of social class differences.